2023
DOI: 10.1021/acs.macromol.2c02434
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Phase Behavior of Bottlebrush Diblock Copolymer-Linear Homopolymer Ternary Blends

Abstract: In this work, we systematically investigated the structure and phase behavior of ternary mixtures containing an AB bottlebrush diblock copolymer and A and B linear homopolymers, where A is polystyrene and B is poly(ethylene oxide), using a combination of small-angle X-ray scattering and cloud point measurements. We found that the overall phase behavior of such mixtures closely resembles the linear counterparts, with lamellae occurring in the copolymer-rich region, macrophase separation in the homopolymer-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
(158 reference statements)
0
3
0
Order By: Relevance
“…This "screening effect" is general in bottlebrush polymers and has been utilized to account for the reduction in χ eff (= 0.03) in PS-PEO bottlebrushes compared with the corresponding linear polymers (= 0.08). 60 Consequently, we speculate that the CUL phase predominates over the Fddd network in ABC bottlebrush block terpolymers. The CUL phase, a combination of cylinders and lamellae, likely has a total free energy that reflects an intermediate curvature to those of the cylinder and lamellae phases.…”
Section: ■ Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This "screening effect" is general in bottlebrush polymers and has been utilized to account for the reduction in χ eff (= 0.03) in PS-PEO bottlebrushes compared with the corresponding linear polymers (= 0.08). 60 Consequently, we speculate that the CUL phase predominates over the Fddd network in ABC bottlebrush block terpolymers. The CUL phase, a combination of cylinders and lamellae, likely has a total free energy that reflects an intermediate curvature to those of the cylinder and lamellae phases.…”
Section: ■ Discussionmentioning
confidence: 86%
“…In comparison to ABC linear terpolymers, the stiffness of the bottlebrush polymers, along with the crowding of side chains around the backbone, must hinder side-chain penetration, thereby screening contact between the A and C domains. This “screening effect” is general in bottlebrush polymers and has been utilized to account for the reduction in χ eff (= 0.03) in PS-PEO bottlebrushes compared with the corresponding linear polymers (= 0.08) . Consequently, we speculate that the CUL phase predominates over the Fddd network in ABC bottlebrush block terpolymers.…”
Section: Discussionmentioning
confidence: 87%
“…Blends of bottlebrush BCPs with homopolymers have attracted some interest as a means to readily shift L 0 . The behavior of these blends mirrors that of blends of linear BCPs with homopolymers, where low M n free chains lead to intermixing with the side chains of the bottlebrush BCP and higher M n tend to partially segregate to the interior of the block. , A study of ternary mixtures (AB/A/B) observed that the addition of low M n free chains resulted in no change in the periodicity regardless of the amount of homopolymer added, as the additive resulted in expansion of the junction parallel to the component interface. This behavior is somewhat different from the case of the linear blends, where low M n additives can lead to some expansion of a j , but this is accompanied by expansion of the lamellae perpendicular to the interface as the mass fraction increases.…”
Section: Introductionmentioning
confidence: 76%
“…Due to the chemical incompatibility between PDMS soft segments and isophorone bis-urea (IPBU) hard segments, IPBU units were apt to form supramolecular aggregates assembled by abundant hydrogen bonds within the PDMS matrix, leading to a distinct phase separation structure. [28][29][30] However, the asymmetric alicyclic structure of IPBU provided a high level of steric hindrance, which facilitated the prevention of crystallization, 31 thus resulting in the weak and dynamic hard phase conducive to optical transparency and autonomous self-healing performance of SHPU-WNS. Taking SHPU-WNS as a template, we proposed a molecular engineering strategy of simultaneously achieving nanostructure transformation and dynamic reinforcement (Fig.…”
Section: Tuning the Nanophase-separation Structure In Soft Self-heali...mentioning
confidence: 99%